Toll‐Like Receptor 3 and 7/8 Function Is Impaired in Hepatitis C Rapid Fibrosis Progression Post‐Liver Transplantation. Issue 4 (20th February 2013) - Howell, J.; Sawhney, R.; Skinner, N.; Gow, P.; Angus, P.; Ratnam, D.; Visvanathan, K.
Abstract : Recurrence of hepatitis C (HCV) postliver transplant is universal, with a subgroup developing rapid hepatic fibrosis. Toll‐like receptors (TLRs) are critical to innate antiviral responses and HCV alters TLR function to evade immune clearance. Whether TLRs play a role in rapid HCV recurrence posttransplant is unknown. We stimulated peripheral blood mononuclear cells (PBMCs) from 70 patients with HCV postliver transplant with TLR subclass‐specific ligands and measured cytokine production, TLR expression and NK cell function. Rate of fibrosis progression was calculated using posttransplant liver biopsies graded by Metavir scoring (F0–4; R = fibrosis stage/year posttransplant; rapid fibrosis defined as >0.4 units/year). Thirty of 70 (43%) patients had rapid fibrosis progression. PBMCs from HCV rapid‐fibrosers produced less IFNα with TLR7/8 stimulation (p = 0.039), less IL‐6 at baseline (p = 0.027) and with TLR3 stimulation (p = 0.008) and had lower TLR3‐mediated monocyte IL‐6 production (p = 0.028) compared with HCV slow fibrosers. TLR7/8‐mediated NKCD56 dim cell secretion of IFNγ was impaired in HCV rapid fibrosis (p = 0.006) independently of IFNα secretion and TLR7/8 expression, while cytotoxicity remained preserved. Impaired TLR3 and TLR7/8‐mediated cytokine responses may contribute to aggressive HCV recurrence postliver transplantation through impaired immune control of HCV and subsequent activation of fibrogenesis. Abstract : In patients who develop rapid HCV‐mediated fi brosis progression post—liver transplantation, peripheral blood mononuclear cells have impaired TLR7/8‐mediated IFNalpha production by plasmacytoid dendritic cells, impaired TLR7/8‐mediated IFNgamma production by NK CD56dim cells and impaired TLR3‐mediated pro‐infl ammatory cytokine production by monocytes in comparison to HCV patients with slow fi brosis progression.